Part II : Critical assessment of financial sector reforms and liberalization of ASEAN 10+5 economies. - Hoo, Jeffery Pek Jhuh. (2008)
The Final Year Project “PART I: RANKING OF 2005 FINANCIAL SECTOR REFORMS AND LIBERALIZATION OF ASEAN 10+5 ECONOMIES” adopted the NTU-ISEAS Financial Reforms and Liberalization Indices (FRLRI) framework (see Ding et al., 2007) which quantifies an economy’s efforts and progress in financial sector reforms and liberalization. This report continues from Part I, with its main objective set in accessing and monitoring the financial sector reforms and liberalization of the ASEAN 10+5 economies from 1993 to 2005.